2009
DOI: 10.1016/j.ssc.2009.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Model of hopping dc conductivity via nearest neighbor boron atoms in moderately compensated diamond crystals

Abstract: Expressions for dependences of the pre-exponential factor σ3 and the thermal activation energy ε3 of hopping electric conductivity of holes via boron atoms on the boron atom concentration N and the compensation ratio K are obtained in the quasiclassical approximation. It is assumed that the acceptors (boron atoms) in charge states (0) and (−1) and the donors that compensate them in the charge state (+1) form a nonstoichiometric simple cubic lattice with translational period Rh = [(1 + K)N ] −1/3 within the cry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 24 publications
(90 reference statements)
3
34
0
Order By: Relevance
“…In this work in the weak electric field limit (e d k T B E  , where d is the mean hop length of electron via localized states) and when the thermal energy is greater than the fluctuation dispersion of energy levels of localized states it is shown that the ratio of the diffusion coefficient to the drift mobility is equal to k T e B . Finally, the values of effective hole or electron concentrations involved in hopping migration via hydrogenlike impurities in crystalline semiconductors are determined in [13,16,17,[28][29][30]. [31][32][33][34] used particular forms of the expressions for N hp and N hn that are only suitable for limiting values of the compensation ratio (K 1  or K 1 1 - ) of the majority impurity by the minority impurity.…”
Section: At Temperatures T T Jmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work in the weak electric field limit (e d k T B E  , where d is the mean hop length of electron via localized states) and when the thermal energy is greater than the fluctuation dispersion of energy levels of localized states it is shown that the ratio of the diffusion coefficient to the drift mobility is equal to k T e B . Finally, the values of effective hole or electron concentrations involved in hopping migration via hydrogenlike impurities in crystalline semiconductors are determined in [13,16,17,[28][29][30]. [31][32][33][34] used particular forms of the expressions for N hp and N hn that are only suitable for limiting values of the compensation ratio (K 1  or K 1 1 - ) of the majority impurity by the minority impurity.…”
Section: At Temperatures T T Jmentioning
confidence: 99%
“…As the concentration of v-band holes increases, their exchange interaction becomes significant [52,57,60]. As a result, the energy of the top of the v-band (E v = 0 for an undoped crystal) shifts deeper into the band gap, decreasing the energy level E per for hole percolation, equation (29), by the value of the exchange energy E exc for a single v-band hole. That is equivalent to the top of the v-band approaching the center of the acceptor band E a and is taken into account in equation (24).…”
Section: Statistics Of Holes In Valence and Acceptor Bandsmentioning
confidence: 99%
See 2 more Smart Citations
“…where Poklonski et al (2009) developed a model of hopping dc conductivity via the nearest boron atoms in moderately compensated diamond crystals. They have assumed that the energy of acceptor levels exhibits the Gaussian distribution due to the fluctuations of the electrostatic interaction of ionized acceptors with other ionized atoms, both acceptors and donors.…”
Section: Introductionmentioning
confidence: 99%